ANALISIS IDIOM DALAM BERITA KRIMINAL DI SURAT KABAR PADANG EKSPRES (KAJIAN SEMANTIK) - najmi hayati; Dwi Muthia Chan; Irawati Rahman (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2018)
This research was conducted to describe the form of idiom in the news of kiminal in Padang Ekspres newspaper and to describe the meaning of idiom in news of crime of Padang Ekspres newspaper. This type of research is qualitative by using the method of padan and agih. Data collected by using method refer and note that is: Technique of collecting data in this research by using method refer and note with step as follows (1) listening to language use in Padang Express newspaper, (2) using the technique of note, the first step is the underlined idiom, after all underlined then the idiom recorded and grouped by type of idiom and make conclusions about the results of research. The results of this study indicate that there is a full idiom type and idiom in part in the news kiminal in newspapers Padang Express. Full idiom found in 5 data while idiom partially found as many as 11 data, that is menahan diri, makan korban, tertangkap basah, lelaki hidung belang, timah panas, nasib nahas, hiburan malam, minuman keras, kepala keluarga, wali kota, dini hari , senjata api, lanjut usia, kereta api , saksi mata, orang tua. More partial idioms are found than full idioms. Overall data found as many as 16 data including idiom